New flexible parametric and semiparametric models for survival analysis - Ramires, Thiago Gentil (2017)
In this work was proposed a new distributions, called log-sinh Cauchy, with has bimodal shapes and can be used as alternative to the mixture models. Based in the proposed distribution, the following models were proposed: Regression model based in the GAMLSS framework; models with cure rate based in the mixture and promotion time models; semiparametric models, modeling the parameters using penalized splies; semiparametric models, using the penalized splines to model the non-linear effects present in the cure rate. For all proposed models, the computational codes were implemented in the R software, with is available along of the document as well as some brief introduction on how to use them.